IMPLEMENTASI KEADILAN RESTORATIF DAN MEKANISME DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK BERDASARKAN UU NOMOR 11 TAHUN 2012 - Udjari, Hendrianto; Saputra, Rio; Darmawan, Didit; Putra, Arif Rachman; Khayru, Rafadi Khan (Gapenas Publisher, 2025)
This study analyzes and evaluates the implementation of the juvenile criminal justice system in Indonesia based on Law No. 11/2012 on the Juvenile Criminal Justice System (UU SPPA), with an emphasis on protecting the rights of children in conflict with the law. Protection of children is a crucial issue, given that children are a vulnerable group prone to exploitation, violence, discrimination, and psychological risks in the conventional criminal justice system, which still has a retributive tone. Legal reform through the UU SPPA has changed the approach to resolving children's cases from repressive to more humane and restorative, including through diversion mechanisms and restorative justice that prioritize the recovery, rehabilitation, and guidance of children rather than punishment alone. This study uses a normative legal method with a literature review of regulations, national and international legal documents, and previous research results. The study results show that the principle of the best protection for children integrated in the SPPA Law has provided a new direction in the juvenile criminal justice system in Indonesia, although its implementation still faces various challenges. These challenges include inconsistencies in understanding and implementation by law enforcement officials, limited resources, insufficient institutional support, and public perceptions that are sometimes still retributive. Future efforts to strengthen the system should focus on ensuring consistent fulfillment of the best interests of the child.